Water management in dam reservoirs – analysis of operational risks on the example of new facilities - Maksymilian Połomski; Mirosław Wiatkowski (Journal of Water and Land Development)
Even during normal hydrometeorological conditions, water management in dam reservoirs requires special measures and difficult operational decisions. The situation becomes even more complicated when high or even extreme surges occur. The study, which focused on four newly constructed dam reservoirs, identified key issues that may result in inappropriate operational assumptions being adopted. These include: (1) uncertainty in the values of characteristic flows – this is particularly true for the Krosnowice reservoir, where calculations were based on only one empirical method, (2) uncertainty in the capacity of the discharge devices – the capacity for bottom outlet of the Szalejów Górny reservoir was shown to be 19.5   m3 ∙ s−1 higher than assumed, (3) consequences of attempts to absolutely maintain permitted outflow – for the analysed reservoirs, in the matter of control flow, it ultimately results in exceeding permitted outflow by values ranging from 123.86% (Roztoki Bystrzyckie reservoir) to 2000% (Krosnowice reservoir), (4) considering the cooperation of facilities located in the same catchment – for the wave of the design flow, delaying the outflow from Szalejów Górny reservoir would allow to reduce the total wave in Kłodzko by 41.37%, (5) the need to prepare the multi-purpose reservoirs for the surge – in the event of a design flow surge it would allow to reduce the surge in Kłodzko from 242 to 101.5 m3 ∙ s−1, however it would require a difficult decision to anticipate emptying the facilities in the interval from 18 h before the surge for Szalejów Górny to 4 h before the surge for Boboszów.